CLASSIFICATION OF INFORMATICS AND INFORMATION TECHNOLOGIES - Andrey A. Mayorov; Vladimir P. Sedyakin (Открытое образование (Москва), 2016)
The article considers the actual question about informatics and information technologies classifi cation. There are the hegemony information technologies over the information sciences and two modern methods of classifi cation: “habitatual” and “conceptual-criterial” method. On the basis of the last the article calls attention to example for classifi cation of science’s nomenclature of VAK.